Effects of Dry Needling on Connectivity of Corticospinal Tract, Spasticity, and Function of Upper Extremity in People with Stroke: Study Protocol for a Randomized Controlled Trial - Masoome Ebrahimzadeh; Noureddin Nakhostin Ansari; Iraj Abdollahi; Behnam Akhbari; Saeideh Monjezi (Journal of Acupuncture & Meridian Studies, 2021)
Background : Spasticity is a common motor disorder in adult stroke patients. Injury to the corticospinal tract (CST) is associated with spasticity. Dry needling (DN) has positive impacts on spasticity reduction and improvement in the range of motion (ROM) in stroke patients. This study aims to investigate the effectiveness of DN on the connectivity of the CST and the level of spasticity in adult stroke patients. Methods : This double-blind randomized controlled trial will enroll and randomly assign stroke patients to either the experimental group, for receiving three sessions of DN for the spastic wrist flexors, or the control group, for sham needling. The primary outcome measures will be diffusion tensor imaging and the Modified Modified Ashworth Scale score to assess CST connectivity and wrist flexor spasticity, respectively. The Box and Block Test and standard goniometry are the secondary outcome measures to assess hand dexterity and active and passive wrist ROM, respectively. Measurements will be taken both before and after the intervention. Discussion: The results of this study will provide important evidence of the effects of DN on CST connectivity, spasticity, and arm function in adult stroke patients. Trial registration: This trial is registered in the Iranian Registry of Clinical Trials (IRCT) (https://www.irct.ir; IRCT20191208045649N1).